2016
DOI: 10.1039/c5gc01976a
|View full text |Cite
|
Sign up to set email alerts
|

Direct upgrading of fast pyrolysis lignin vapor over the HZSM-5 catalyst

Abstract: Continuous fast pyrolysis of lignin and direct upgrading of pyrolysis vapor by the HZSM-5 catalyst produce renewable aromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 46 publications
4
70
0
Order By: Relevance
“…Fast pyrolysis (FP) of the pinewood produced a water‐free basis bio‐oil (organic fraction) yield of 51.3 %. As expected, the elemental analysis of the FP oil shows oxygen composition similar to its biomass precursor, i. e. 38.7 % versus 42.8 %, respectively. This implies the inefficacy of a pure thermal degradation to effectively deoxygenate the intermediate volatiles that eventually condenses into the organic liquid product .…”
Section: Resultssupporting
confidence: 78%
“…Fast pyrolysis (FP) of the pinewood produced a water‐free basis bio‐oil (organic fraction) yield of 51.3 %. As expected, the elemental analysis of the FP oil shows oxygen composition similar to its biomass precursor, i. e. 38.7 % versus 42.8 %, respectively. This implies the inefficacy of a pure thermal degradation to effectively deoxygenate the intermediate volatiles that eventually condenses into the organic liquid product .…”
Section: Resultssupporting
confidence: 78%
“…By pyrolysis of the individual components of lignocellulosic biomass, Wang and co‐workers have found that dehydration is the primary pathway to remove oxygen in the ex situ CFP of lignin over HZSM‐5, and the phenolic compounds generated from the thermal decomposition of lignin are prone to form coke/char . Zhou and co‐workers have developed a continuous fast pyrolysis reactor to upgrade lignin pyrolysis vapors over coupled HZSM‐5 catalysts through an ex situ CFP process . At 600 °C, 70 wt % of oxygen‐free aromatics (mainly benzene and toluene) can be obtained in the organic liquid product.…”
Section: Upgrading Lignin Pyrolysis Vapors By Cracking and Aromatizamentioning
confidence: 99%
“…reactor to upgrade lignin pyrolysis vaporso ver coupled HZSM-5 catalysts through an ex situ CFP process. [41] At 600 8C, 70 wt %o fo xygen-free aromatics (mainly benzene and toluene)c an be obtained in the organic liquid product. In general, HZSM-5-based catalysts show good performance for lignin conversion by the ex situ CFPp rocess.B oth an improvement in the catalyst and better reactord esign are necessary to achieve ahigher yield of aromatics from lignin.…”
Section: Ex Situ Cfp Of Modelcompoundsmentioning
confidence: 99%
“…However, the detailed contributions of H 2 O, CO and CO 2 to the overall deoxygenation as a function of cracking temperature are scarcely reported in the literature. A reason for this situation might be a lack of the accurate data of water yield at least in some cases, since the water determination could be largely interfered by the dehydration of HZSM-5 itself (Zhou et al, 2016). In our experiment, the design of a bypass line in the reactor system (Fig.…”
Section: Insight Into the Catalytic Effects Of Hzsm-5mentioning
confidence: 99%
“…In all above two-stage pyrolysis experiments, however, the composition of bio-oil was reckoned in the light of peak areas of GC-MS or MB-MS. Most recently, Zhou et al (2016) presented an investigation into the catalytic upgrading of fast pyrolysis lignin vapor with HZSM-5. The yields of main light aromatics such as BTXN and light hydrocarbon gases (CH 4 , C2-C3) were quantitatively determined.…”
Section: Introductionmentioning
confidence: 99%